Supply chain concentration and corporate financialization - Zou, Meifeng; Zhang, Xindong (Frontiers in Psychology, 2023)
We investigate whether firms that rely on major suppliers or customers (i.e., with a higher supply chain concentration) tend to hold more financial assets than other firms due to supply chain pressure. We find that firms with a higher supply chain concentration have a higher financialization level. The firms’ competitive power reduces their financialization level but cannot reverse the adverse impact of supply chain concentration. Furthermore, we explore the mechanism underlying the relationship between supply chain concentration and corporate financialization using the mediation effect method. We find that the supply chain concentration impairs firms’ main business profitability, leading firms to hold more financial assets. The main business profitability channels play partial mediating roles. Our findings reveal that overdependence on large suppliers/customers causes firms to escape reality and adopt virtual economics.